Circulating microRNAs Profile in Patients With Transthyretin Variant Amyloidosis - Vita, Gian Luca; Aguennouz, M’Hammed; Polito, Francesca; Oteri, Rosaria; Russo, Massimo; Gentile, Luca; Barbagallo, Cristina; Ragusa, Marco; Rodolico, Carmelo; Di Giorgio, Rosa Maria; Toscano, Antonio; Vita, Giuseppe; et al. (Frontiers in Molecular Neuroscience, 2020)
Transthyretin variant amyloidosis (ATTRv) is a rare autosomal dominant disease characterized by the accumulation of amyloid in many organs, mostly causing a sensory-motor neuropathy, cardiomyopathy, and dysautonomia. The aim of the study was to report microRNAs (miRNAs) expression profile identified in the blood of ATTRv patients. Ten ATTRv patients, 10 asymptomatic carriers of transthyretin variant (TTRv), 10 patients with Charcot-Marie-Tooth (CMT) disease, and 10 healthy controls were studied. Human Schwann cells cultures were used to study the regulatory effects of miR-150-5p on the expression of cAMP response element-binding protein (CREB), brain-derived neurotrophic factor (BDNF), and nerve growth factor (NGF). ATTRv patients had 33 miRNAs up-regulated and 48 down-regulated versus healthy controls; 9 miRNAs were up-regulated and 30 down-regulated versus CMT patients; 19 miRNAs were up-regulated and 38 down-regulated versus asymptomatic TTRv carriers. Twelve out of the 19 upregulated miRNAs had a fold increase higher than 100. The validation experiment indicated miR-150-5p as a valuable biomarker to differentiate ATTRv patients from asymptomatic TTRv carriers (AUC: 0.9728; p < 0.0001). Schwann cells culture model demonstrated that miR-150-5p is a powerful negative regulator of CREB, BDNF, and NGF genes. Identification of deregulated miRNAs can help in understanding the complex pathomechamism underlying the development of ATTRv and related multisystemic pathology. Further investigations are needed on the role of circulating miR-150-5p to predict the shift of TTRv carriers from an asymptomatic status to symptoms appearance.